Social Cognitive Theory for Arabic Reading Skills: A Quasi-Experimental Study in an Indonesian Islamic Junior High School - Dian Tsuroya Patria Ummah; M. Abdul Hamid; Nur Hasan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Reading ability constitutes a fundamental life skill that is not limited to the academic context but also plays a vital role in social interaction. Through reading activities, learners can broaden their knowledge and deepen their understanding across various fields. To increase students’ motivation in learning Arabic, particularly in improving their reading competence, teachers should implement effective and engaging instructional strategies. One of the effective approaches is the method grounded in Albert Bandura's Social Cognitive Theory (SCT). This study aims to analyze The Albert Bandura’s Social Cognitive Theory on improving students’ reading skills at Bahrul Ulum Junior high school. The research employed a quantitative approach with a quasi-experimental design. The sample consisted of 39 students (n = 20 experimental; n = 19 control) selected through purposive sampling. Data were collected via observation, documentation, and a pretest-posttest instrument comprising multiple-choice reading comprehension items and Arabic oral reading tests. The findings are as follows: first, the implementation of SCT was operationalized through three instructional stages, the opening stage, the core application stage, and the closing stage. During the core stage, four SCT components were systematically activated: attention (students observed the teacher modeling fluent Arabic reading), retention (students encoded pronunciation patterns and intonation), reproduction (students practiced oral reading independently and in pairs), and motivation (students received constructive feedback and positive reinforcement). Second, the application of this theory produced a statistically significant effect on reading skill improvement. The experimental class demonstrated higher mean score gains than the control class, with differences of 9.25 versus 4.84 on the oral reading test, and 17.5 versus 11.57 on the multiple-choice comprehension test. Paired sample t-test results yielded p = 0.00 (p < 0.05) for both instruments, leading to the rejection of H₀ and acceptance of Hₐ. Effect size analysis using Cohen's d indicated a large effect for oral reading (d = 1.24) and a medium effect for reading comprehension (d = 0.46), confirming the practical significance of the intervention. These findings suggest that Albert Bandura's Social Cognitive Theory can positively support students' reading development in similar Arabic language learning contexts. Nevertheless, generalizability should be interpreted cautiously given the single-site setting and relatively small sample size. Future research involving larger and more diverse samples across multiple institutions is recommended to further validate these findings